Aproximación al monacato occidental en la Edad Media - Padrón, Héctor Jorge (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2003)

(untitled)
Monasticism was not born nor grew up in contraposition to scholasticism. Both of them express the truth and unity of religious life. In this paper, the Author analyses the cases of a monk and a scholar, Bernardus of Claraval and Petrus Abelardus, respectively, by means of two of their major works: Commentary on The Song of Songs and Preface to the Commentary on the Letters of Saint Paul. Finally, a brief summary concerning longing for heaven in texts of Medium Ages is included.